ANALISIS PENINGKATAN PERKERASAN LENTUR KE PERKERASAN KAKU PADA RUAS JALAN BUARAN - BENDANPETE STA 0+00 - 1+700 JEPARA JAWA TENGAH . - Junaidhi, Afif; Adi Saputro , Yayan; Hidayati, Nor (Jurnal Civil Engineering Study, 2024)
Afif Junaidhi, Nim 191230000357, Analysis of the improvement of flexible pavement to rigid pavement on the buaran - bendanpete sta 0+00 - 1+700 jepara central java road 2023., Yayan Adi Saputro, S.T., M.T., Nor Hidayati, S.T., M.T., Civil Engineering, Faculty of Science and Technology1, Nahdlatul Ulama University1 Jepara1. With roads, everyone can increase their mobility while fulfilling important activities. As time goes by and the length of service lasts, road conditions eventually decline, both in terms of service level and structural condition. The method used for analysis of rigid pavement on roads is the 2017 Pavement Design Manual1 Method and the method used for planning road surface drainage dimensions refers to SNI 03-3424-1994 concerning Procedures for Road Surface Drainage Planning. The results of rigid pavement planning research calculations using the 2017 Pavement Design Manual method resulted in a concrete plate thickness of 275 mm, a thin concrete layer1 (LMC) of 100 mm, a class A aggregate drainage layer of 150 mm. Connections in rigid pavement are divided into two, namely longitudinal connections with tie bars using Ø 161- 6001 threads, and transverse connections with dowels using plain reinforcement D 32 - 300. The material used is planned to use concrete. The calculation results obtained are that the channel base width is 65 cm, the wet channel height is 35 cm, and the guard height is 40 cm